2013
DOI: 10.1039/c3mt00111c
|View full text |Cite
|
Sign up to set email alerts
|

The CTR/COPT-dependent copper uptake and SPL7-dependent copper deficiency responses are required for basal cadmium tolerance in A. thaliana

Abstract: Copper (Cu) homeostasis in plants is maintained by at least two mechanisms: (1) the miRNA-dependent reallocation of intracellular Cu among major Cu-enzymes and important energy-related functions; (2) the regulation of the expression of Cu transporters including members of the CTR/COPT family. These events are controlled by the transcription factor SPL7 in Arabidopsis thaliana. Cadmium (Cd), on the other hand, is a non-essential and a highly toxic metal that interferes with homeostasis of essential elements by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 79 publications
(140 reference statements)
1
59
0
6
Order By: Relevance
“…From what is known, genes encoding Cu transporters COPT1, COPT2, COPT3, and COPT6 are expressed in pollen grains of Arabidopsis (Sancenรณn et al, 2004;Gayomba et al, 2013;Jung et al, 2012;Bock et al, 2006). AtCOPT3 is expressed early in pollen development, while At-COPT1 is expressed at later stages (Bock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…From what is known, genes encoding Cu transporters COPT1, COPT2, COPT3, and COPT6 are expressed in pollen grains of Arabidopsis (Sancenรณn et al, 2004;Gayomba et al, 2013;Jung et al, 2012;Bock et al, 2006). AtCOPT3 is expressed early in pollen development, while At-COPT1 is expressed at later stages (Bock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both transcription factors (TFs) regulate gene expression during Cu deficiency through binding to Cu deficiency-responsive elements (59-GTAC-39) in promoters of their targets (Sommer et al, 2010;Yamasaki et al, 2009;Quinn et al, 2000;Birkenbihl et al, 2005;Garcia-Molina et al, 2014;Kropat et al, 2005). Recent transcriptome analyses revealed that SPL7 is required for the expression of the iron (Fe)/Cu reductase oxidases, FRO4 and FRO5, and several Cu transporters, including members of the copper transporter family, COPT1 and COPT2, that together constitute the high-affinity Cu uptake system (Bernal et al, 2012;Gayomba et al, 2013;Jung et al, 2012;Yamasaki et al, 2009;Jain et al, 2014). Among other SPL7-regulated genes are COPT6, members of the yellow stripe-like transporter family, YSL2 and YSL3, and the Cu chaperone CCH, which together contribute to Cu transport to photosynthetic tissues and Cu remobilization from sources to sinks upon senescence (Bernal et al, 2012;Gayomba et al, 2013;Jung et al, 2012;Yamasaki et al, 2009;Chu et al, 2010;Himelblau et al, 1998;Mira et al, 2001;Himelblau and Amasino, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Barcelรณ et al, 1988;Jung et al, 2015Jung et al, , 2016Lagriffoul et al, 1998;. ํŠนํžˆ ์นด๋“œ๋ฎด์— ์˜ํ•ด ๋ฐœ์ƒ๋œ ์‚ฐํ™”์  ์ŠคํŠธ๋ ˆ์Šค๋Š” ํ™œ์„ฑ์‚ฐ์†Œ์ข…์˜ ์„ธํฌ ๋‚ด ์ถ• ์ ์œผ๋กœ ์ธํ•˜์—ฌ ํƒ„์ˆ˜ํ™”๋ฌผ, ๋‹จ๋ฐฑ์งˆ, ์ง€์งˆ ๋ฐ ํ•ต์‚ฐ์˜ ์ƒํ•ฉ์„ฑ์— ๋ถ€์ •์ ์ธ ์˜ํ–ฅ์„ ๋ฏธ์น˜๊ณ  ์‚ฐํ™” โ€ค ํ™˜์› ํ•ญ์ƒ์„ฑ์„ ๊ต๋ž€ํ•˜์—ฌ ์ • ์ƒ์ ์ธ ์ƒ์ฒด ๊ธฐ๋Šฅ์„ ์ €ํ•ดํ•œ๋‹ค (Gayomba et al, 2013;Singh and Agrawal, 2010;Singh et al, 2006, Xu et al, 2014.…”
Section: Introductionunclassified